GAS TURBINES CONNECTED BEFORE HOT WATER BOILERS - Penninger, Antal; Fülöp, Zoltán; Czinkóczky, Botond; Móricz, István; Kóbor, Ágota (Periodica Polytechnica Mechanical Engineering, 1991)
Due to the efficiency of heat utilization equipment connected after gas turbines, the use of this equipment is widespread. This study examines the use potential of gas turbines connected before hot water boilers, also widely used in Hungary, to determine, in addition to electric power production, how reliable operation can be maintained with as little modification of the heat utilization equipment as possible. The recommendation is suitable for electric power production in both normal and peak operation since it retains the original burners together with their blowers. This study has been made in relation to boilers in Hungary, of about 15 PTVM-I00 units and 1 PTVM-180 unit. This study includes the basic parameters of the gas turbine, the parameters needed to determine its energy conditions, the recommendation for the so-called canal burner placed after the gas turbine and the power engineering parameters of the boiler.